Dyslexia as One of The Problem in Pedodontic Treatment - Hayatun Safrina (Journal of Dentistry Indonesia, 2015)
Generally we do not know about the presence of the barrier that cause the children, students, or patients to have dyslexia, i.e. difficulties in learning abilities on writing, spelling, speaking and counting. Physicians and dentists also face some difficulties in treating them, and sufferers are often improperly treated. At home they may be treated as if they had a physical defect, and in the school as if they were dull-witted students. Dyslexia has the characteristic of continually adhering to the patient until adult and then old age. There is no prevention for this condition, but the patient can be helped by excavating their existing potential. However, for this purpose it is necessary that the parent, educators, physicians, dentists, helpers, and people in general are aware about dyslexia.